(untitled) (Texas Journal of Philology, Culture and History, 2024)
In world linguistics, particularly in Uzbek linguistics, the study of nonverbal means of verbal communication (various states of voice, gestures, facial expressions, and body movements) has been conducted in various aspects of the language. The realities of modern life show that communication in today’s world is characterized by extreme freedom, unpredictability, and distance from language rules. In this context, the role of nonverbal means has increased more than ever, and they have begun to carry a significant pragmatic load. Especially their use in virtual communication is often overlooked by researchers. This article provides a brief overview of virtual communication, its study level, and its importance. It also analyzes the nonverbal forms used in communication. Furthermore, the linguistic and nonlinguistic connections, their mutual influences and contradictions, and the opportunities to create a certain image are discussed. The characteristics of nonverbal means in the communication process are also highlighted. Additionally, the communication process among Uzbeks and the forms of interaction they use are given. The results of a survey on gender-specific communication traits in Uzbek culture are also presented.